PERKEMBANGAN KOGNITIF ANAK USIA 4-5 TAHUN DI TK ISLAM IBNU QOYYIM KEC. MEDAN SELAYANG SETIA BUDI TAHUN AJARAN 2019/2020 - Fatma Gustina; Khadijah Khadijah (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2020)
The purpose of this study was to determine the cognitive development of children aged 4-5 years in Islamic Kindergarten Ibnu Qoyyim Kec. Medan at a glance, Setia Budi. This research method is qualitative, which uses observation, interview, and documentation instruments. Analysis of the data used is data collection, data reduction, data display and draw conclusions. Research findings show (1) children's cognitive development is developed through several methods, such as playing, playing arithmetic, learning while playing with gometry, conducting science experiments and various methods that are creatively packaged by the teacher. (2) the cognitive development of children in Ibnu Qoyyim's kindergarten develops, seen from the child's observation sheet, 7 out of 8 cognitive development with satisfactory value. (3) teacher creativity and teacher methods are very important influences in the development of cognitive programs in Ibn Qoyyim Kindergarten. The obstacle in children's cognitive development is that children rarely attend school.